An Isomeric Copper‐Diisophthalate Framework Platform for Storage and Purification of C2H2 and Exploration of the Positional Effect of the Methyl Group. Issue 21 (17th May 2021) - Lin, Shengjie; Fan, Lihui; Zhou, Ping; Xu, Tingting; Jiang, Zhenzhen; Hu, Simin; Chen, Jingxian; He, Yabing
Abstract: Three isostructural metal‐organic frameworks (MOFs) based on dicopper paddlewheels and dimethyl‐functionalized linear diisophthalate ligands were solvothermally constructed, with the aim to investigate their performance regarding acetylene (C2 H2 ) storage as well as separation and purification and to further understand the positional effect of the weakly polarized methyl functionality. Isotherm measurements and IAST selectivity analyses revealed that the three compounds exhibited the promising potential for storing C2 H2 and recovering C2 H2 from carbon dioxide (CO2 ) and methane (CH4 ) at ambient conditions. Furthermore, their C2 H2 adsorption properties can be tailored and optimized by altering the relative position of the methyl substituents immobilized in the organic linkers. At 298 K and 1 atm, the C2 H2 uptake capacities vary from 173.0 to 183.6 cm 3 (STP) g −1, while the C2 H2 /CH4 and C2 H2 /CO2 adsorption selectivities are in the range of 24.5–26.6 and 4.34–4.70 for the equimolar gas mixtures. The ortho ‐dimethyl‐modified MOF outperformed better than the other two MOF isomers. The results indicate that rational arrangement of functional groups can to some extent improve gas adsorption properties. Although the property discrepancy caused by the less‐polar methyl group is not as large as that by Lewis‐basic nitrogen atoms, this is the first experimental demonstration of the positional effect of methyl group on C2 H2 adsorption. Abstract : A family of NbO‐type MOFs based on three isomeric diisophthalate ligands functionalized by dual methyl groups but at different positions was constructed, exhibiting promising potential for C2 H2 storage and purification, and the structure‐property correlation was investigated, revealing the positional effect of methyl functionality on selective C2 H2 adsorption.